Risk Management in Indonesian Local Government: A Literature Study - Amirya, Mirna; Irianto, Gugus (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
The primary objective of this research is to provide an in-depth understanding of the concept of risk management in Indonesian local governments, specifically focusing on the legal frameworks and cultural aspects surrounding risk awareness. The research employs a literature review methodology, utilizing articles, research journals, and 30 open-access local risk management regulations. Data analysis follows Miles and Huberman's qualitative approach, involving four key phases: data collection, data reduction, data presentation, and conclusion/review. The study reveals that some Indonesian local governments have established legal frameworks for risk management since approximately 2017. Key elements for effective risk management include a culture of risk awareness, robust risk management processes, effective communication and consultation, and sound assessment and reporting practices. The development of a risk-aware culture involves communication of risk understanding across all organizational levels, internalization of risk management in decision-making processes, and the enhancement of a control environment supporting a risk- aware culture. While this research sheds light on the progress of risk management in Indonesian local governments, there may be limitations inherent in the study, such as the scope of literature available and potential variations in local practices. The implication of these findings suggests the need for further research to delve deeper into specific regional contexts and challenges that may impact the effectiveness of risk management.